Death in paradise. Season thirteen [videorecording (DVD)] - Thorogood, Robert (BBC, 2024)
The sun-soaked, smash-hit whodunnit returns for more murder mysteries with a light touch and a warm heart. DI Neville Parker and the team are back on the idyllic Caribbean Island of Saint Marie with more ingenious murders to solve. In the 100th episode, Selwyn celebrates 50 years of police service and comes face to face with a surprising enemy. Meanwhile in the rest of the series, Marlon confronts his future, Naomi lets loose, and Catherine's old friend becomes a murder suspect. There's a deadly game of bingo, a cookery competition poisoning, death during a blackout and a mystifying murder in a lift. And with new and returning faces arriving on the island, can Neville open to love? Also includes the 2023 Christmas Special: It's Christmas in the Caribbean and Neville's larger-than-life mum, Melanie, is in town. She quickly assimilates herself in with the rest of the team, but she's disheartened to see how down in romance Neville is, given everything he's been through the past two years. Can she instill some festive cheer in her unlucky-in-love son? Elsewhere, a wealthy business owner called Gerry is found dead at the bottom of a ravine. It could just be an accident, but Gerry's ominous last words 'It's behind you' suggest something more is going on. And things take an even stranger turn when the team discover that the family's house guest has mysteriously vanished, prompting her fiancé to fly out on a rescue mission.